Variability in English-Spanish bilingual phonotactics: A look at sC clusters - Tetzloff, Katerina (Journal of Monolingual and Bilingual Speech, 2024)
Spanish prohibits initial sC clusters. Past studies have reported that this phonotactic restriction results in the perception of an illusory /e/, ‘repairing’ the illicit sequence (e.g., spid perceived as espid). Because English allows sC clusters, English-Spanish bilinguals are confronted with conflicting phonotactic systems. The present study investigated if this locus of phonotactic conflict yields bilingual variability (i.e., non-monolingual-like language behavior). Spanish monolinguals and English-Spanish bilinguals performed a nonce word judgment task, whereby they assigned acceptability ratings to sC-initial nonce words. Monolinguals were highly unaccepting of sC-initial words, whereas bilinguals were more likely to accept them as phonotactically licit, showing evidence of bilingual variability. The bilingual variability was constrained by English phonotactics, as sC clusters were rated as significantly more acceptable than other illicit onset clusters that are illicit in both languages. Furthermore, the monolinguals failed to show evidence of an illusory vowel effect, highlighting the importance of task type in phonotactic perception studies.